An Indefinite Type Equation Involving Two P-Laplacians - Ramos-Quoirin, H (2012)
We study a problem involving the operators -?+W and its p-homogeneous version -?p+V. The existence of three non-negative solutions is obtained under indefinite type conditions on these operators. To this aim, we proceed by minimization of the energy functional on open parts of the Nehari manifold. © 2011 Elsevier Inc.